Closing forensic psychiatric hospitals in Italy: a new revolution begins?. (June 2015) - Barbui, Corrado; Saraceno, Benedetto
Summary: On 30 May 2014 the Italian Parliament approved a new law regarding forensic psychiatric hospitals. Forensic psychiatric hospitals are facilities that admit individuals who have committed a criminal offence but lack criminal responsibility because of a mental disorder and are deemed as dangerous to public safety. Here we report the key aspects of the new legislation together with some critical considerations.